Hearing Loss among the Traffic Police in Kathmandu Valley – finding from a pilot cross-sectional study - Bista, Madhab Raj; Dahal, Pranab (International Journal of Occupational Safety and Health, 2016)
Background: Noise induced hearing loss has been increasing rapidly with the advancement of technological, industrial and anthropogenic growth. Hearing loss is identified to be minimizing psychosocial well-being of an individual and reduced economic activities apart from deafness. This study aimed to measure the noise induced health impairment in traffic polices of Kathmandu valley. Methods and Materials: The cross-study was conducted among eighty traffic police in the Kathmandu and Lalitpur districts of Nepal. Purposive stratified sampling method was used for the study. A semi structured interview guide was developed to assess the physical findings and an audiometric test were also conducted with each individual traffic personnel to assess the hearing impairment. Results: The study identified Chabahil in Kathmandu with highest level of noise at 90 A-weighted decibel. Overall, moderate hearing loss in the left ear was reported in 55% of the respondents and mild hearing list in right ear in 46.3% of the respondents. The study found bilateral moderate hearing loss in all the respondent serving more than twenty years in traffic management. The effects of getting tired (80%), difficulties in concentration (76.3%) and increased irritation (72%) were identified as the high ranked health effects. Conclusion: The study reinforces the need of further exploration as this occupational health issue is a growing public health concern.